Incident cancers and late mortality in Australian children treated by allogeneic stem cell transplantation for non‐malignant diseases. Issue 1 (26th September 2016) - Nelson, Adam S.; Vajdic, Claire M.; Ashton, Lesley J.; Le Marsney, Renate E.; Nivison‐Smith, Ian; Wilcox, Leonie; Dodds, Anthony J.; O'Brien, Tracey A.; ,
Abstract: Background: Hematopoietic stem cell transplantation (HSCT) is a life‐saving procedure for children with a variety of non‐malignant conditions. However, these children face an increased risk of late death and incident cancers after HSCT, which may occur many years after their initial HSCT. Procedure: We examined cancer occurrence and late mortality in a population‐based cohort of 318 Australian children who underwent allogeneic HSCT for non‐malignant disease. Standardized incident ratios (SIRs) and standardized mortality ratios (SMRs) were calculated and compared with population controls. Results: We identified six (1.9%) cancers at a median 9.2 years post‐HSCT. Cancer occurred 15 times more frequently than in the general population (SIR 15.4, 95% CI = 6.9–34.2). Of the 198 patients who survived for at least 2 years post‐HSCT, 11 (5.6%) died at a median 7.5 years post‐HSCT. The mortality rate was 17 times higher than in the general population (SMR 17.5, 95% CI = 9.7–31.2). Discussion: Children transplanted for non‐malignant conditions require evidence‐based survivorship programs to reduce excess morbidity and mortality.